2018
DOI: 10.1111/asj.13030
|View full text |Cite
|
Sign up to set email alerts
|

Genome‐wide association studies identified variants for taurine concentration in Japanese Black beef

Abstract: We performed genome-wide association studies (GWAS) using the BovineSNP50 array to detect significant single nucleotide polymorphisms (SNPs) that may affect the concentration of 22 free amino acids and three peptides in Japanese Black beef cattle. A total of 574 Japanese Black cattle and 40,657 SNPs from the array were used for this study. Genome-wide significant SNPs were detected for β-alanine (three SNPs on chromosomes 22 and 29) and taurine (26 SNPs on chromosome 22). Importantly, the top two SNPs for taur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Also the RUVBL1 gene nearby appears to contribute to thermos-tolerance mechanisms in African cattle [ 47 ]. The EEFSEC gene in the same region was identified having a pleiotropic effect in milk traits in Nordic Holstein (Cai et al, 2020) and amino acid concentration in Japanese Black beef cattle [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…Also the RUVBL1 gene nearby appears to contribute to thermos-tolerance mechanisms in African cattle [ 47 ]. The EEFSEC gene in the same region was identified having a pleiotropic effect in milk traits in Nordic Holstein (Cai et al, 2020) and amino acid concentration in Japanese Black beef cattle [ 48 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, the mtDNA haplogroup P has been identified at a high frequency in Japanese Shorthorn cattle, indicating that the propagation root of Nambu-ushi differs from that of other Japanese native cattle (Mannen et al, 2020;Noda et al, 2018). Uemoto et al (2017) and Sasago et al (2018) also identified the allele frequencies of beef palatability genes in four breeds (Japanese Black, Japanese Brown, Japanese Shorthorn, and Holstein), and those of the Japanese Shorthorn were completely different from those of the other three breeds. Thus, the genetic background of the Japanese Shorthorn is unique among Japanese Wagyu breeds, and the native livestock breed must be conserved.…”
Section: Pedigree Completeness and Generation Intervalsmentioning
confidence: 98%
“…The PLAG1 zinc finger ( PLAG1 ), fatty acid synthase ( FASN ), cytochrome P450 family 7 subfamily B member 1 ( CYP7B1 ) and stearoyl‐CoA desaturase ( SCD ) genes are already known to harbor mutations that affect meat quality traits and fatty acid composition in cattle . In this study we genotyped these five SNPs in longissimus dorsi muscle of 1000 Hanwoo steers (Table S1) using TaqMan SNP genotyping assays (LSK) (Table S2).…”
Section: Association Of Fasn1 Fasn2 Cyp7b1 Plag1 and Scd Snps Withmentioning
confidence: 99%